Neighborhood social capital is associated with participation in health checks of a general population: a multilevel analysis of a population-based lifestyle intervention- the Inter99 study - Bender, Anne Mette (BMC Public Health, 2015)
BACKGROUND: Participation in population-based preventive health check has declined over the past decades. More research is needed to determine factors enhancing participation. The objective of this study was to examine the association between two measures of neighborhood level social capital on participation in the health check phase of a population-based lifestyle intervention. METHODS: The study population comprised 12,568 residents of 73 Danish neighborhoods in the intervention group of a large population-based lifestyle intervention study - the Inter99. Two measures of social capital were applied; informal socializing and voting turnout. RESULTS: In a multilevel analysis only adjusting for age and sex, a higher level of neighborhood social capital was associated with higher probability of participating in the health check. Inclusion of both individual socioeconomic position and neighborhood deprivation in the model attenuated the coefficients for informal socializing, while voting turnout became non-significant. CONCLUSION: Higher level of neighborhood social capital was associated with higher probability of participating in the health check phase of a population-based lifestyle intervention. Most of the association between neighborhood social capital and participation in preventive health checks can be explained by differences in individual socioeconomic position and level of neighborhood deprivation. Nonetheless, there seems to be some residual association between social capital and health check participation, suggesting that activating social relations in the community may be an avenue for boosting participation rates in population-based health checks. TRIAL REGISTRATION: ClinicalTrials.gov (registration no. NCT00289237). ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12889-015-2042-5) contains supplementary material, which is available to authorized users.